A geometric morphometric study of sex differences in the scapula, humerus and ulna of Chaetophractus villosus (Xenarthra, Dasypodidae) - Acuña, Francisco (2017)
Sexual differences in some of the components of the pectoral girdle and forelimb of Chaetophractus villosus (Desmarest, 1804) were investigated by means of geometric morphometrics. A total of 15 scapulae (7 males, 8 females) and 50 humeri-ulnae complexes (24 males, 26 females) were examined. No size differences were detected between sexes for any of the bones, but shape differences were found for the humerus and the ulna that enhance the in-forces or the related in-levers. Females had a more robust humerus, with an enlarged deltoid tuberosity, a more spherical head, higher tubercular and epicondylar widths, and more developed supracondylar crests. The ulna of the females was characterised by a more pronounced curvature along its main axis, a caudal displacement of the lateral fossa, a longer olecranon, and a deeper trochlear notch. For both bones, the discriminant analysis classified correctly all the specimens according to their sex. A small percentage of the variance (5.2% for the humerus; 6.8% for the ulna) was explained by allometry. The morphological traits found for the humerus and ulna of the females suggest an increased structural strength that could result in powerful digging strokes while keeping shoulder and elbow stabilisation, suggesting a fossorial advantage over males.